2021
DOI: 10.1108/jhtt-01-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do eReferral, eWOM, familiarity and cultural distance predict enrollment intention? An application of an artificial intelligence technique

Abstract: Purpose Little empirical attention has been paid to the effects of electronic word-of-mouth (eWOM), electronic referral (eReferral), familiarity and cultural distance on behavioral outcomes, especially within the context of educational tourism. Based on the social network theory, this paper aims to explore the effects of eReferral, eWOM, familiarity and cultural distance on enrollment intention. Design/methodology/approach Survey data (n = 931) were obtained from educational tourists using a judgmental sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
4
6
0
Order By: Relevance
“…This study also supported the fourth hypothesis that eWOM significantly influences the travel intention of tourists from Europe and Oceania. This is consistent with previous investigations such as Abubakar (2016), Jalilvand and Heidari (2017), Chen et al (2014), andOday et al (2021). eWOM is a new platform and is used as a marketing tool.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also supported the fourth hypothesis that eWOM significantly influences the travel intention of tourists from Europe and Oceania. This is consistent with previous investigations such as Abubakar (2016), Jalilvand and Heidari (2017), Chen et al (2014), andOday et al (2021). eWOM is a new platform and is used as a marketing tool.…”
Section: Discussionsupporting
confidence: 92%
“…Jalilvand and Heidari (2017) found that eWOM has a more positive effect on attitude and travel plans than WOM. Online reviews affect how tourists act and plan to act (Oday et al, 2021), but eWOM readers must evaluate them (Verma & Dewani, 2021). Iriobe et al (2019) found that eWOM did not affect tourists' intention to revisit Nigerian religious destinations.…”
Section: Ewom As a Mediator Rolementioning
confidence: 99%
“…The overly stereotyped communication method has not really aroused the audience's interest in traditional culture but also reduced the aesthetic charm of traditional culture itself, losing its due temperature and vitality. Therefore, how to avoid the patterned dissemination of artificial intelligence and inject the temperature, depth, and height of traditional culture into artificial intelligence technology is an urgent problem to be solved [11].…”
Section: Introductionmentioning
confidence: 99%
“…They also say that familiarity with the brand "is a subjective evaluation of the experience, the amount of information and the level of knowledge accumulated by consumers about a specific place or experience" (p. 957). Finally, Oday et al (2021) argue that familiarity Dávila Garza H., Alarcón Martínez, G. J. & López Pérez, J. F. ISSN 2386-7876 -© 2023 Communication & Society, 36(1), 47-64 "has a notable influence on consumer decision-making processes, such as their intention to continue using a site" (p. 4).…”
Section: Familiarity (Of User With News Website)mentioning
confidence: 99%